Chlorine Solutions for a Safe Method of Decontamination of Breast Pump Milk Collection Kits Before and After the Coronavirus Disease 2019 Pandemic - Rigourd, Virginie; Mouadh, Benali; Poupon, Joel; Langrand, Jerome; Goutard, Arnaud; Droguet, Christine; Bille, Emmanuel; Frange, Pierre; Bahri, Yasmina; Pasquier, David; Lapillonne, Alexandre; Skurnik, David (Frontiers in Nutrition, 2021)
To promote breast feeding and breast pumping is essential for the most vulnerable infants even if the current COVID-19 pandemic sanitary crisis imposes more stringent hygienic measures. As recommended by the Center for Disease Controle of Prevention (20020), World Health Organization (2020) and Milk Bankindg Association (2020) “after each pumping session, all pump part that come into contact with breast milk should be appropriately disinfected”. The present study proposed different methods than can be used and focuses on the safety analysis of chlorine solution (CS) in terms of residual HCA and THM. We also performed an efficacy testing of the CS approach to decontaminate the devices used to collect the milk (breath-pumps and bottles). The bacteriologic results of 1982 breast pump milk samples collected in three different settings showed a major decrease of the microbial contamination using either sterile device or decontaminate with CS compared to a simple soap washing. The main messages from our study are to propose a guideline for the safe use of CS and to define situations when breast pump decontamination might be necessary: vulnerable babies for which sterile device is recommended, special circumstances, for example the current COVID-19 pandemic, special situations, for example women living in precarious conditions, or women pumping their milk at work but that would have low or no access to boiled water. Overall, cold decontamination reduced losses of milk for bacteriological reasons in human milk banks and may also be interesting to prevent horizontal contamination by virus like COVID-19.